zIndex – Benchmarking Municipalities in Public Procurement - Jiri Skuhrovec; Jan Soudek (Charles University in Prague, Institute of Economic Studies (IES), 2016)
This paper presents a methodology and first results of the zIndex - a public procurement benchmarking tool for contracting authorities that measures a deviation from best practice recommendations. zIndex is a composite index mapping many issues in the areas of openness, competition and transparency. Indirectly it measures efficiency and corruption potential in public procurement. The pilot application of our methodology on a sample of 194 Czech municipalities and their procurement in the period 2011-2013 worth 3 billion EUR showed several remarkable results such as very low share (30%) of public procurement on actual purchases volume or large portion (50%) of contracts that were cancelled or modified. Finally we find correlation of zIndex with procurement law violations and detected price savings. This implies, that proposed measure of best practice relates both to efficiency and legality, making it usable metric for various further research as well as practical monitoring of procuring agencies.
Keywords: H57; C43; 330; public procurement; transparency index; efficient public control; benchmarking municipalities